Pengaruh Kompensasi, Lingkungan Kerja, dan Kepuasan Kerja terhadap Turnover Intention Karyawan pada PT. Quri Villas - The Chandi Boutique Resorts and Spa (Hotel The Chandi Senggigi) - Syaiful Amri; Rosyia Wardani; Kristi Maria Magdalena (Universitas Bumigora, 2021)
This study aims to examine the effect of compensation, work environment, and job satisfaction to the turnover intention, partially and simultaneously. This type of study is associative research. Technique data collection using observation, interviews, and questionnaires. Population in this study were all employees as many as 60 employees. Sampling technique using probability sampling. The research variables consisted of 3 (three) variables independent namely compensation (X1), work environment (X2), and job satisfaction (X3) and the dependent variable, namely turnover intention (Y). The data were obtained by distributing 60 questionnaires to the respondents who were at Hotel The Chandi Boutique Resorts & Spa. Data analysis technique used is multiple linear regression analysis. The results of the study show that the compensation variable of work environmental, and job satisfaction partially have a significant opposite direction effect on turnover intention. Variable compensation, work environment, and job satisfaction simultaneously has a significant effect on turnover intention. Result this study is also able to show that the independent variables (compensation, work environment, job satisfaction ) are able to explain the dependent variable, (turnover intention ) of 67%, while the remaining 33% turnover intention is influenced by other variables outside of compensation, work environment, job satisfaction